HUBUNGAN ANTARA KADAR PB DALAM DARAH DENGAN KEJADIAN HIPERTENSI PADA OPERATOR SPBU DI KOTA YOGYAKARTA - Rosyidah, Hesti; Djannah, Sitti Nur (Universitas Ahmad Dahlan, 2010)
Background: The spread of Pb to humans could cause many negative effects to health such as cardiovasculer system, hypertension and carsinogenic. The change of society pattern from agrarian to industry and life style, community social economic became was one of the things that cause the increasing of un infected prevalence, that was hypertension. The average of hypertension prevalence in Indonesia around 8,3 percent. Low concentrate of Pb inside blood (3-5 g/dl) had cause effect to blood pressure and Pb also took act in hypertension patolgy. The air pollution in Yogyakarta city alraedy reach the normal standar of air quallity. One of the area with high air pollution was Public Refueling Station (SPBU). The operator employee has high risk to conteminate by dangerous chemical substances especially plumbum by gasoline and motor vehicle gas emission that waiting queue refuelingor vehivle that depart after refueling. The purpose of this study was to determine the relationship of Pb concentrate inside blood with hypertension incident to SPBU operator in Yogyakarta city.Method : This was observational analytic using cross sectional approach with quantitative method. Sample of this study was operator in four SPBU Yogyakarta city amount 25 people. To analyzed Pb concentrate inside blood used spectrophotometry with AAS method, the measuring of blood pressure used mercury sphygmomanometer and respondent characteristic used interview orientation. Data analysis used univariate and bivariate.Result : There was significant relationship between Pb concentrate in blood with hypertension incident to SPBU operator Yogyakarta city with signicancy value (p) amount 0,028 p=0,028 < ?=0,05, the risk seen by RR value = 2,619 (95% CI:0,944-7,625) ; so Ho which mention there was no relationship between Pb concentrate inside blood with hypertension incident to SPBU operator rejected. Ha which mention there was relationship between Pb concentrate inside blood with hypertension incident to SPBU operator accepted.Conclusion : Pb concentrate inside blood had significant relationship with hypertension incident to SPBU operator Yogyakarta city.Keywords : Plumbum (Pb), Hypertension, Public Refueling Station operator